The ILO’s maritime labour convention - Guan, Wenqian. (2011)
With the increasing awareness of how human factors can affect the productivity, efficiency and quality of work, not to mention safety, we should start to be more concerned about the welfare of our people: how they perceive their working conditions, whether they are satisfied with the existing rules and regulations, or is there any area that we can work on to improve.When the vessel is at sea, hundreds of miles away from shore, only the people onboard the vessel can solve the problems encountered. The attitude of the seafarers may decide the fate of the whole vessel and the cargoes onboard. Therefore, it is critical to ensure that the seafarers are fully committed to their work. One way to achieve this is to promote seafarers’ welfare, providing better terms of employment, and decent working conditions.